Enantioselective Palladium-Catalyzed Decarboxylative Dearomative Asymmetric Allylic Alkylation of Benzofurans: Diversity-Oriented Synthesis of Flavaglines - Lu, Hai-Hua; Cao, Meng-Yue (Synlett, 2021)
With the introduction of new Trost-type bisphosphine ligands bearing a chiral cycloalkane framework, the highly efficient and enantioselective palladium-catalyzed decarboxylative dearomative asymmetric allylic alkylation (AAA) of benzofurans was achieved. This enabled a diversity-oriented synthesis (DOS) of previously unreachable flavaglines, which features two diversification stages. A new avenue for developing flavagline-based drugs was thus established.1 Introduction2 The Dearomative Asymmetric Allylic Alkylation of Benzofurans3 Synthesis of Flavaglines4 Conclusion and Outlook
Keywords: palladium catalysis; dearomative asymmetric allylic alkylation (AAA); total synthesis; flavaglines; diversity-oriented synthesis (DOS); N-heterocyclic carbene (NHC) catalysis; benzoin condensation